Phagocyte activity reflects mammalian homeo- and hetero-thermic physiological states - Pikula, Jiri; Heger, Tomas; Bandouchova, Hana; Kovacova, Veronika; Němcová, Monika; Papezikova, Ivana; Piacek, Vladimir; Zajíčková, Renata; Zukal, Jan (BMC veterinary research, 2020)
BACKGROUND: Emergence of both viral zoonoses from bats and diseases that threaten bat populations has highlighted the necessity for greater insights into the functioning of the bat immune system. Particularly when considering hibernating temperate bat species, it is important to understand the seasonal dynamics associated with immune response. Body temperature is one of the factors that modulates immune functions and defence mechanisms against pathogenic agents in vertebrates. To better understand innate immunity mediated by phagocytes in bats, we measured respiratory burst and haematology and blood chemistry parameters in heterothermic greater mouse-eared bats (Myotis myotis) and noctules (Nyctalus noctula) and homeothermic laboratory mice (Mus musculus). RESULTS: Bats displayed similar electrolyte levels and time-related parameters of phagocyte activity, but differed in blood profile parameters related to metabolism and red blood cell count. Greater mouse-eared bats differed from mice in all phagocyte activity parameters and had the lowest phagocytic activity overall, while noctules had the same quantitative phagocytic values as mice. Homeothermic mice were clustered separately in a high phagocyte activity group, while both heterothermic bat species were mixed in two lower phagocyte activity clusters. Stepwise regression identified glucose, white blood cell count, haemoglobin, total dissolved carbon dioxide and chloride variables as the best predictors of phagocyte activity. White blood cell counts, representing phagocyte numbers available for respiratory burst, were the best predictors of both time-related and quantitative parameters of phagocyte activity. Haemoglobin, as a proxy variable for oxygen available for uptake by phagocytes, was important for the onset of phagocytosis. CONCLUSIONS: Our comparative data indicate that phagocyte activity reflects the physiological state and blood metabolic and cellular characteristics of homeothermic and heterothermic mammals. However, further studies elucidating trade-offs between immune defence, seasonal lifestyle physiology, hibernation behaviour, roosting ecology and geographic patterns of immunity of heterothermic bat species will be necessary. An improved understanding of bat immune responses will have positive ramifications for wildlife and conservation medicine.
Keywords: Behavior, Animal; Animals; Erythrocyte Count; chování zvířat; zvířata; Phagocytes; tělesná teplota; Blood Chemical Analysis; Body Temperature; biochemická analýza krve; Chiroptera; počet erytrocytů; fagocyty